A Review of Technology Acceptance of mHealth in India - Ms. Rekha Prasad; Dr. Megha Bhatia (The Bioscan, 2025)
In developing economies especially facing significant resource limitations. delivering healthcare services poses a substantial challenge for governments. With the potential to considerably mitigate health-related issues in the long run the utilization of mHealth (mobile health) emerges as a promising solution providing a proactive tool for preventive healthcare. However, comprehensive studies are scarce on the mHealth technology adoption, particularly in India. In mobile health (mHealth) literature, the purpose of this review is to investigate how technology acceptance is measured and understood. The objective is to identify potential gaps, compare with existing models and definitions of how acceptance is the treated in mHealth research, and clarify the process of technology acceptance. To evaluate the logical implementation of mobile health services and to identify appropriate research domains, a conscientious literature review was conducted, leading to the selection of the framework Technology Acceptance Model (TAM). Performance Expectancy (PE), Social Influencer (SI), Effort Expectancy (EE), Facilitating Conditions (FC), Perceived Reliability, Attitude towards Behavior (ATB), and Privacy and Security (P&S) are the seven additional variables that this study adds to the TAM that Davis first proposed. Various viewpoints are connected to the acceptance of technology, and only a limited number align with existing definitions. Published definitions in the literature were presented separately, potentially contributing to incompatible usage. Establishing a framework for definitions would bring adherence to the reporting of results making it easier to replicate and compare studies. Technology Acceptance consolidates existing definitions, outlines distinct phases of technology acceptance, and provides definitive terminology. As the culmination of this investigation, the research not only adds theoretical value by extending the Technology Acceptance Model (TAM) but also provides practical insights into the adoption of mHealth services in India, guiding policymakers and academics in comprehending and addressing the opportunities and challenges associated with mHealth adoption.